Dekolonisasi Ekonomi dan Konservasi Hutan Berbasis Adat dalam Kosmologi Ekologis Masyarakat Tepera di Distrik Ravenirara Kabupaten Jayapura - Efraim Mangaluk; Yulius Gae Lada; Paulus Mandibondibo; Frank Leonardo Apituley; Amadion Andika Wanaputra; Silvans Tande Bura (Universitas Muhammadiyah Sorong, 2026)
The ecological crisis of the Anthropocene demands a re-evaluation of the technocratic conservation paradigm, which tends to subordinate the ontologies of Indigenous peoples. This study aims to reconstruct the ecological cosmology of the Tepera indigenous community in Yongsu Desoyo Village, Ravenirara District, Jayapura Regency, and to formulate a model of economic decolonization grounded in local wisdom. Employing a critical ethnographic approach through in-depth interviews with customary leaders and participant observation, the research is framed by Habermasian Modernity theory and a Critical-Practical Policy perspective. The findings reveal three principal results. First, the philosophy of Bu Suwe Kani Suwe (The Power of Water is the Power of Land) articulates a triadic water-land-tree paradigm that constitutes the ontological foundation of pre-colonial conservation practices, while the concept of Desoyo as